Cabdio occidentalis, a new species from Lake Mashkid basin and the Makran region (Teleostei: Danionidae) - Jouladeh-Roudbar, Arash; Lalramliana; Vatandoust, Saber; Ghanavi, Hamid Reza; Freyhof, Jörg (Zootaxa, 2023)
Cabdio occidentalis, new species, is described from the Lake Mashkid basin and the Makran region of Iran. It is distinguished from other species of the genus by a combination of characters: 38–42+1–2 total lateral-line scales, 19–23 predorsal scales, 9–11 pectoral-fin rays, and the absence of a keel between the pelvic-fin base and the genital papilla. The cytochrome c oxidase subunit I (COI) sequence separates C. occidentalis from C. morar, its closest congener, by a p-distance of 5.5%.